Effects of Serotonin 2C Receptor Agonists on the Behavioral and Neurochemical Effects of Cocaine in Squirrel Monkeys - Manvich, Daniel F. (The American Society for Pharmacology and Experimental Therapeutics, 2012)
Accumulating evidence indicates that the serotonin system modulates the behavioral and neurochemical effects of cocaine, but the receptor subtypes mediating these effects remain unknown. Recent studies have demonstrated that pharmacological activation of the serotonin 2C receptor (5-HT(2C)R) attenuates the behavioral and neurochemical effects of cocaine in rodents, but such compounds have not been systematically evaluated in nonhuman primates. The present experiments sought to determine the impact of pretreatment with the preferential 5-HT(2C)R agonist m-chlorophenylpiperazine (mCPP) and the selective 5-HT(2C)R agonist Ro 60-0175 [(α-S)-6-chloro-5-fluoro-α-methyl-1H-indole-1-ethanamine fumarate] on the behavioral and neurochemical effects of cocaine in squirrel monkeys. In subjects trained to lever-press according to a 300-s fixed-interval schedule of stimulus termination, pretreatment with either 5-HT(2C)R agonist dose-dependently and insurmountably attenuated the behavioral stimulant effects of cocaine. In subjects trained to self-administer cocaine, both compounds dose-dependently and insurmountably attenuated cocaine-induced reinstatement of previously extinguished responding in an antagonist-reversible manner, and the selective agonist Ro 60-0175 also attenuated the reinforcing effects of cocaine during ongoing cocaine self-administration. It is noteworthy that the selective agonist Ro 60-0175 exhibited behavioral specificity because it did not significantly alter nondrug-maintained responding. Finally, in vivo microdialysis studies revealed that pretreatment with Ro 60-0175 caused a reduction of cocaine-induced dopamine increases within the nucleus accumbens, but not the caudate nucleus. These results suggest that 5-HT(2C)R agonists functionally antagonize the behavioral effects of cocaine in nonhuman primates, possibly via a selective modulation of cocaine-induced dopamine increases within the mesolimbic dopamine system and may therefore represent a novel class of pharmacotherapeutics for the treatment of cocaine abuse.